Thermoelectricity Based on Cuo as a Semiconducting Material - El-Agez, Taher M; El-Ghamri, Hatem S; Abdel-Latif, Monzir S; Taya, Sofyan A; Alkanoo, Anas A (International Journal of Chemistry and Materials Research, 2014)
In this paper, thermoelectricity based on copper(II) oxide CuO as semiconducting material is explored. The electrical properties of the samples were studied under different temperature gradients and pressures. Moreover, the effect of baking temperature was also investigated. CuO prepared using decomposition of Cu(NO3)2 as well as CuO nanopowder prepared using microwave-assisted synthesis technique were investigated and their results were compared. It was found that the current density can be enhanced with increasing the pressing pressure of the sample and when the sample undergoes a baking process. Moreover, it was found that the current density can be considerably enhanced with increasing the temperature gradient between the two ends of the sample. The CuO prepared using microwave-assisted synthesis technique was found to exhibit much better results over those of the CuO prepared using decomposition of Cu(NO3)2.